2016
DOI: 10.1186/s12939-016-0480-z
|View full text |Cite
|
Sign up to set email alerts
|

Non random distribution of child undernutrition in Ethiopia: spatial analysis from the 2011 Ethiopia demographic and health survey

Abstract: BackgroundChild undernutrition showed geographical inequalities due to variations in contextual determinants from area to area which indicates that location is an important factor in child undernutrition. However, there are limited studies on spatial epidemiology of child undernutrition in Ethiopia. This study was aimed to identify the SaTScan spatial clusters of child undernutrition in Ethiopia.MethodsNutritional indices of children (0–59 months) with Global Positioning System (GPS) location data were accesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 16 publications
(17 reference statements)
8
36
0
Order By: Relevance
“…The town has a longitude of 382,667 (3816′0.120″ E) and latitude of 63,167 (619′ 0.012″ N) with altitude of 1776. The dominant ethnic group in the area is Gedeo and most of the people speak Gedeo-Offa language [31]. The town has two sub-divisions.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The town has a longitude of 382,667 (3816′0.120″ E) and latitude of 63,167 (619′ 0.012″ N) with altitude of 1776. The dominant ethnic group in the area is Gedeo and most of the people speak Gedeo-Offa language [31]. The town has two sub-divisions.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Such high rates of unintended pregnancy and its possible series repercussion justify a study of their negative consequences on child nutrition and growth, especially when considering that adverse nutritional outcomes in a child are more likely to occur if the pregnancy was unintended. In addition, the study area is one of the areas with the highest burden of malnutrition [31] and very poor family planning utilization in the country [32]. This study hypothesized that high number of unintended pregnancies that could be resulted from poor family planning in the study area might be contributed for such significant burden of under-five malnutrition Therefore, the study was designed to assess the association of unintended pregnancies and other family and child characteristics with the nutritional status of children, particularly with regard to stunting among children under 5 years old.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges for improving child health are more pronounced in the resource-limited countries with chronic fiscal deficits, high dependence on foreign donors and low-performing agriculture sector. Poor agricultural resources with chronic water and energy crisis generally result in higher dependency on imported food and inflation in consumer prices, with diminishing food security among the poor households 13 43–47. The burden of stunting gets further compounded by the fast-changing demography, labour market and sociocultural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have shown that child undernutrition clusters in specific regions in developing countries (Fenn, Morris, & Frost, 2004;Gebreyesus, Mariam, Woldehanna, & Lindtjorn, 2016) and different types of spatial analysis studies have been conducted to identify geographical inequalities in child stunting (Fenn et al, 2004, Gebreyesus et al, 2016, Adekanmbi, Uthman, & Mudasiru, 2013, Alemu, Ahmed, Yalew, & Birhanu, 2016. However, much less has been done on explaining the factors that contribute to spatial variability in stunting (Di Cesare et al, 2015;Haile, Azage, Mola, & Rainey, 2016;Sharaf & Rashad, 2016;Srinivasan, Zanello, & Shankar, 2013), particularly in India.…”
mentioning
confidence: 99%